Design of Glegeg-in Modern Drink Positioning Improvement Based on Perceptual Mapping Using Multidimensional Scaling Method - Afra Ghaida Hana; Yati Rohayati; Ima Normalia Kusmayanti (Budapest International Research and Critics University, 2022)
Glegeg-in is a Bandung-based brand that sells modern drink such as milk tea, thai tea, coffee, and boba drinks. Glegeg-in revenue have been unstable over the past years. One of the root causes is a low brand awareness compared to its competitors. A low brand awareness compared to other brands caused by the customers not aware of the value proposition that Glegeg-in offers, which is affordable, has a variety of menu options, and attractive packaging. The purpose of this research is to design a positioning improvement system to minimize the instability of Glegeg-in revenues by mapping the position of Glegeg-in and its competitors through perceptual mapping using the multidimensional scaling method. 122 modern drink customers were employed as samples in this research input data. Furthermore, the input data is used for data processing using MDS which produces a perceptual mapping. Based on the results of perceptual mapping, three areas of competition were obtained, Glegeg-in is in the same area with Happy Fat, which makes it the closest competitor of modern drink brands. The results of this study are an integrated positioning system improvement design for Glegeg-in on the attributes of modern drinks which are the value proposition of Glegeg-in. This is the basic consideration for Glegeg-in in achieving the goals that have been set.